SCIENTIFIC FUNDAMENTALS OF FORMING REGIONAL ADAPTIVE STRATEGY OF HYDROSYSTEM MANAGEMENT (ON THE EXAMPLE OF THE VORSKLA RIVER IN POLTAVA REGION) - Pysarenko, P. V.; Samoilik, M. S.; Taranenko, A. O.; Ts’ova, Yu. А.; Prystavsʹkyy, M. M. (Scientific Progress & Innovations, 2021)
The article deals with investigating chemical, physical-chemical and hydro-biological parameters of water in the Vorskla. The relationship between anthropogenic loading and water quality has been established. The direct relationship between N, P content in water and the development of blue-green algae has also been determined. The resistance of aquatic ecosystems to anthropogenic eutrophication in four areas of the Vorskla was assessed. The areas having better production processes were singled out. Area T.1 of the Vorskla is capable of self-cleaning. The aquatic ecosystem of T.2-T.4 areas produces more organic matter than it can decompose, which reduces its ability to self-purification and intensifies eutrophication processes. The reduction of anthropogenic loading on the studied sections of the Vorskla was estimated by the P/D ratio. On the basis of the obtained results agro-ecological recommendations for regulating eutrophication of water systems were developed for the existing, optimal and perspective scenarios and their economic efficiency was determined. According to the current scenario, the damage from water pollution makes UAH 62 million annually. The optimal scenario (during 2022–2030) includes the following measures: the use of probiotics (the total amount of 720 kg in 4 areas during 5 years); construction of modern wastewater purification systems with using probiotics); reduction of wastewater from cesspits (by using biopreparations and replacing them with septic preparations). The perspective scenario (for 2030–2040) includes the following measures: construction of rainwater and melt water collection system; cleaning of bottom sediments by using hydro-biological methods; re-cultivation of solid domestic wastes landfills (by liming and using of probiotics). To solve the top-priority measures of the 1-st stage, UAH 43 million are necessary. The approximate implementation period is 8 years. After implementing these methods, the damage from water pollution will be reduced by 85 % and will amount to UAH 9.3 million. The implementation of optimal measures covers the losses in the amount of UAH 52.7 million and will have the economic efficiency of UAH 9.7 million per year. During 8 years of implementing measures, the economic effect will make about UAH 378.6 million. UAH 70.8 million is necessary to fulfill all perspective measures. The compensation of losses from water pollution as a result of implementing these measures makes 15 % (UAH 9.3 million). Improving the aquatic ecosystem of the Vorskla river will enable to reduce the environmental risks to public health, promote the development of recreation and fisheries (social and economic effect).